PEMBERDAYAAN LANSIA MELALUI KARANG WERDA DI DESA NGLEGOK KECAMATAN NGLEGOK KABUPATEN BLITAR - Rifqi Firda S, Afiyatur Rosidah Lusiana Devika F.s (Forum Ilmu Sosial, 2016)
Elderly coral is a social organization that is not widely known by the public. Reefs Werdha a container coaching and empowerment Elderly. Elderly is a part of society that is closely related to public welfare issues. The realization of the government's efforts in empowering the elderly is the introduction of services for the elderly through several levels of health services at the community level is one of them through the Coral Werdha. Program of Coral Werdha that Posyandu where this program can help the elderly in accordance with their needs, so that the elderly do not feel anymore neglected in society. This study focuses on the welfare of the elderly in terms of physical and material terms. The method used is a qualitative method approach through interviews and direct observation. The results of this study indicate that prior to the Coral Elderly seniors less noticed by the people around. After the Coral Elderly seniors feel their welfare isguaranteed in the form of free health care facilities and the provision of such basic commodities that are held regularly every month.